PURCHASE DECISION ANALYSIS THROUGH PRICE AND PRODUCT QUALITY - Edi Rahmat Taufik (International Journal of Social Science, 2021)
The purpose of this study is to determine the results of the analysis of purchasing decisions through price and product quality. This type of research is quantitative analysis using survey methods and sampling techniques using incidental sampling techniques, where consumers who come to marketing locations fill out questionnaires. The number of samples analyzed was 97 respondents. The data analysis method used is multiple regression analysis, using SPSS software (statistical package for social science) version 26.0 as a data analysis tool. The results showed that the price variable had a significant positive effect on purchasing decisions and product quality had a positive and significant effect on purchasing decisions. Furthermore, price and product quality simultaneously have a positive and significant effect on purchasing decisions